Analysis of Regional Revenue and Expenditure Budget Realization Reports at the Financial Agency of the Mountainous Papua Provincial Government - Meiles Yigibalom; Jetty E. H. Mokat; Sisca B. Kairupan (PT. AHLAL PUBLISHER NUSANTARA, 2026)
This study aims to describe and analyze the preparation process of the Regional Revenue and Expenditure Budget (APBD) Realization Report at the Regional Financial Agency (BPPKAD) of Mountainous Papua Province. Using a qualitative descriptive method with a phenomenological approach, data were collected through triangulation techniques: observation, in-depth interviews, and documentation. The study focused on four sub-foci: the realization of physical and financial reporting (RFK), reporting timeliness, conformity of agency reports with the APBD, and the preparation of the Governor's Accountability Report (LKPJ). The findings reveal that while coordination and reporting mechanisms exist, challenges persist. Realization reporting (RFK) is coordinated periodically, primarily to accelerate absorption evaluation. Reporting schedules are staggered, with annual reports due within three months post-fiscal year. However, conformity is assessed based on adherence to budget calendars, digital reporting order, and accuracy of expenditure details, yet hindered by limited accounting human resources and geographical challenges. The LKPJ is prepared through consolidated performance and financial data. The study concludes that the reporting process is not yet optimal, facing significant obstacles in human resource capacity, inter-agency coordination, and infrastructure, which affects the timeliness and accuracy of financial accountability. Recommendations include substantial investment in human resource capacity building and reinforcement of digital reporting systems. Keywords: APBD Realization, BPPKAD, Budget Reporting, Financial Accountability, Mountainous Papua, Public Financial Management